Tourism Development Plan in Nigeria: Implementation, Management and Sustainability - Aina , Olayinka Christopher; Agboola, Mayowa Olugbenga (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
The Management of sustainable tourism is recognized as an important aspect of tourism planning, this process is now receiving even greater attention from relevant government agencies. Thus, in managing sustainable tourism development therefore, the adoption of planning and management techniques and process in developing sustainable goals and objectives is very paramount. In general, recent studies in the field of tourism have identified well planned and well managed tourism policy as the panacea to sustainable tourism development. The paper focus on the process and the challenges involved in the implementation and management of the Nigeria tourism development plan vis-a-vis the effort of the Nigeria Tourism Development Corporation (NTDC) in the planning and management of tourism facilities and destinations in the country. Findings revealed that though the final master plan has not been officially released since the draft was published in year 2006, implementation of the draft plan has suffered a lot of political and administrative bottlenecks which has utilizes the benefits of tourism to that community, government and private activities. The paper therefore recommends the full implementation of the tourism master plan which will only be effective with the collaborative efforts of all stakeholders in the tourism industry in aspects of finding, planning and management of tourism development in Nigeria for effective sustainability.